Institutional support mechanisms in vocational counselling for adolescents without a valid family support - Grazioli, Porfirio (Social Welfare: Interdisciplinary Approach, 2011)
In many countries the concept of institutional support in vocational counselling for risk group youngsters has rather wide understanding and interpretation. Presented theoretical and practical Christian issue reveals a profi le, as much as possible close to the Model of Vocational Counselling for teenagers without a valid family support. The needs that are common to this group of youngsters have special characteristics, and in this way could be described as special needs. To these special needs and necessities are added those deriving from the ways of management of living in a community, when this is based on the pedagogical methods of the so-called selfgovernment. Therefore, the role of institution and institutional support plays signifi cant role in the successful integration process of teenagers without a valid family support into the labour market.